Knowing What we Mean, Meaning What we Say: The Humpty Dumpty Maxim of Online Interaction - Cook, Julian; Jacobs, Neil (Proceedings of the International Conference on Networked Learning, 2004)
This paper examines ‘discussion’ in a case study involving online learning, in which both tutor and students assessed the discussion board as having failed. An explanation for this is sought via analyses that draw from Fairclough’s critical discourse analysis and, in particular, the ideas of genre and discourse. Two sets of discourses are identified and linked with specific interaction genres. Data from the discussion board and an interview with the tutor are then shown to exhibit both confusion and tension between these discourses and genres. The paper suggests that effective online interaction requires that we ensure that expectations are both clear and appropriate to the learning model being pursued.